2019
DOI: 10.1111/ajag.12616
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and adjustments in maintaining health and well‐being of older Asian immigrants in New Zealand: An integrative review

Abstract: Objective There is a paucity of health‐related research on older Asian immigrants in New Zealand. The aim of this review was to critically examine literature on the health and well‐being of this population group. Methods An integrative literature review was conducted from December 2017 to February 2018. Online databases searched were Scopus, MEDLINE, CINAHL and the Australia/New Zealand Reference Centre. Results Two themes were identified: Firstly, the “challenges stemming from an unfamiliar environment” faced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
(141 reference statements)
0
7
0
Order By: Relevance
“…In Australia, research shows that many older immigrants may be unwilling to access health care services due to limited English proficiency and cultural beliefs and knowledge [ 11 ]. Review papers in Canada [ 12 ], the United States [ 13 ], and New Zealand [ 14 ] all have pointed to similar challenges faced by older immigrants in terms of access barriers related to language, cultural values and beliefs, inequitable resources, access barriers, and various structural challenges. In the United Kingdom, research has indicated that social care services have usually left the older immigrants out [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, research shows that many older immigrants may be unwilling to access health care services due to limited English proficiency and cultural beliefs and knowledge [ 11 ]. Review papers in Canada [ 12 ], the United States [ 13 ], and New Zealand [ 14 ] all have pointed to similar challenges faced by older immigrants in terms of access barriers related to language, cultural values and beliefs, inequitable resources, access barriers, and various structural challenges. In the United Kingdom, research has indicated that social care services have usually left the older immigrants out [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, they were not familiar with the services and support that they could seek for help. Second, in line with the finding of "following adult children's advice," older Chinese immigrants become the more vulnerable member in the parent-child relationship and lose their financial independence and social status after migrating to a new country (Jetten et al, 2018;Montayre et al, 2019;Shuang et al, 2019). Hence, they might avoid complaining about memory loss, which might trouble their children and make them impatient.…”
Section: Differences Between the Melbourne And Beijing Groupsmentioning
confidence: 92%
“…Lack of language proficiency (Batalova & Fix, 2010), cultural adaptability (Campion, 2018), lack of local work experience and qualifications, non-recognition of foreign qualifications (Khan-Gökkaya & Moesko, 2021), lack of credential recognition and short-term visas (Alho, 2020) are some of the challenges migrants face in searching for employment in their host countries. A large amount of literature is available on employability challenges faced by Indians (Kaur, 2019;Montayre et al, 2019), Africans (Bartley, 2010;Rosewarne & Shuker, 2010;Tuwe, 2018), Chinese (Gong et al, 2020;Ran & Liu, 2021;Wang & East, 2020;), Asians as a whole (Ho, 2003;Wong, 2015), Fiji Indians (Aporosa, 2012Pio & Dana, 2014). However, only a minimal amount of literature on the challenges faced by SL migrants in NZ is available.…”
Section: Introductionmentioning
confidence: 99%